Pramipexole Responsive Neck Numbness: The Therapeutic Role of Dopamine Agonists in the Spinal Cord Indicating to a Common Spinal Pathophysiology with Restless Leg Syndrome (RLS)? - Yulug, Burak; Hanoglu, Lütfü (Current Clinical Pharmacology, 2016)
Background: There is still speculative data regarding the role of spinal dopaminergic neurotransmission in restless leg syndrome (RLS). Methods: We evaluated the therapeutic role of pramipexole in a patient with cervical disc prolapsus who exceptionally presented with neck restlessness. Results: We have found that pramipexole leads to a significant improvement in restlessness symptoms in the neck region. Discussion: The therapeutic role of pramipexole may not only suggest secondary deficits due to spinal pathologies but also indicate that specialized spinal dopaminergic neurons may play an important role in the pathogenesis of region specific restlessness symptomatology.
Keywords: restlessness leg syndrome